Analysis of Errors of Grade X Students in Solving Arithmetic Sequence Story Problems - Satriawan, M Agus (Lembaga Riset Mutiara Akbar, 2025)
This study aims to analyze the errors made by tenth-grade students of Central Lombok Senior High School in solving word problems on arithmetic sequences. This type of research is descriptive qualitative with 30 tenth-grade students in one of the high schools as research subjects. Data were obtained through written tests in the form of arithmetic sequence story problems and semi-structured interviews. Error analysis was conducted based on Newman's theory, including reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. The results showed that the most dominant errors occurred at the transformation stage (34%), where students had difficulty converting verbal problems into mathematical forms. In addition, process skill errors (28%) also often appeared because students did not correctly apply the arithmetic sequence formula. These findings provide implications that learning needs to be improved through a contextual approach and intensive word problem practice to improve students' conceptual and procedural understanding.